Efektivitas pemberian tamulawak (Curcuma xanthorrhiza Robx) terhadap kelangsungan hidup dan pertumbuhan berat relatif ikan Nila (Oreochromis niloticus) - Milki Sidik; S Suriansyah; M Rozik (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2020)
The research implemented in wet labs Department of Fisheries Faculty of Agriculture University of Palangkaraya with the allocation of time of 40 days commencing from February, 27th 2019 to april,7th 2019. This study aimed to the effectivity of ginger (Curcuma xanthorrhiza Roxb) of the survival tilapia (Oreochromis niloticus). The research used a pool tarp that is given nets 12 units with a size of 1x1x1 meters and filled with fish samples as many as 40 fishes/net. Fish samples used are tilapia fish with a size of 2 to 3. The experimental design used is RAL (completely randomized design) with 4 treatments with 3 replications. Treatment A (control), treatment B (addition of ginger 3 g/kg feed), treatment C (the addition of ginger 6 g/kg feed), and treatment D (addition of ginger 9 g/kg feed). The results determine the effect of ginger treatment D (additions ginger 9 g/kg feed) in increase survival rate that was 84.1% and growth relative weight that was 1966.72% and the value feed conversion 3.1. Keywords : Ginger, survival rate, tilapia fish.